PROSES INTEGRASI DAN STRATEGI KOMUNIKASI KELOMPOK MINORITAS PENGHAYAT KAPRIBADEN DALAM KULTUR DISKRIMINATIF DI DESA CANDIPARI, PORONG, SIDOARJO - Nurhalizah, Mevy Eka (LP2M IAIN Tulungagung, 2020)
This paper tries to illustrate how the process of social integration and communication strategies of minority groups in the Kapribaden community in discriminatory culture in Candipari Village, Porong District. This paper uses a descriptive method with field observations, interviews and documentation studies. The results of the study show that the integration process occurred due to three discrimination experienced by the Kapribaden group namely the prohibition of ritual worship in Candipari and Candi Sumur, coercion to return to Islam and the prohibition on using village graves for followers who died. Among the three phases of integration, the integration is still in the accommodation phase. The phase in which collaboration is still being carried out despite differences of understanding. That is because there are the same interests and goals. In the accommodation phase, compromise and tolerance are reached, where two or more opponents become equally strong. While the communication strategy undertaken by the Kapribaden group is to use translation by providing resistance.